Rooting depth as a key woody functional trait in savannas. Issue 5 (12th May 2020) - Zhou, Yong; Wigley, Benjamin J.; Case, Madelon F.; Coetsee, Corli; Staver, Ann Carla
Summary: Dimensions of tree root systems in savannas are poorly understood, despite being essential in resource acquisition and post‐disturbance recovery. We studied tree rooting patterns in Southern African savannas to ask: how tree rooting strategies affected species responses to severe drought; and how potential rooting depths varied across gradients in soil texture and rainfall. First, detailed excavations of eight species in Kruger National Park suggest that the ratio of deep to shallow taproot diameters provides a reasonable proxy for potential rooting depth, facilitating extensive interspecific comparison. Detailed excavations also suggest that allocation to deep roots traded off with shallow lateral root investment, and that drought‐sensitive species rooted more shallowly than drought‐resistant ones. More broadly across 57 species in Southern Africa, potential rooting depths were phylogenetically constrained, with investment to deep roots evident among miombo Detarioids, consistent with results suggesting they green up before onset of seasonal rains. Soil substrate explained variation, with deeper roots on sandy, nutrient‐poor soils relative to clayey, nutrient‐rich ones. Although potential rooting depth decreased with increasing wet season length, mean annual rainfall had no systematic effect on rooting depth. Overall, our results suggest that rooting depth systematically structures the ecology of savanna trees. Further work examining other anatomical and physiological root traits should be a priority for understanding savanna responses to changing climate and disturbances.